A comparison of the clinical, laboratory and epidemiological features of two divergent subpopulations of Plasmodium knowlesi - Hu, Ting Huey; Rosli, Nawal; Mohamad, Dayang Shuaishah Awang; Kadir, Khamisah Abdul; Ching, Zhen Hao; Chai, Yaw Hung; Ideris, Nur Naqibah; Ting, Linda S.C.; Dihom, Adeline A.; Kong, Sing Ling; Wong, Edmund K.Y.; Sia, Jenny Euk Huong; et al. (Springer Nature, 2021)
Plasmodium knowlesi, a simian malaria parasite responsible for all recent indigenous cases of malaria in Malaysia, infects humans throughout Southeast Asia. There are two genetically distinct subpopulations of Plasmodium knowlesi in Malaysian Borneo, one associated with long-tailed macaques (termed cluster 1) and the other with pig-tailed macaques (cluster 2). A prospective study was conducted to determine whether there were any between-subpopulation differences in clinical and laboratory features, as well as in epidemiological characteristics. Over 2 years, 420 adults admitted to Kapit Hospital, Malaysian Borneo with knowlesi malaria were studied. Infections with each subpopulation resulted in mostly uncomplicated malaria. Severe disease was observed in 35/298 (11.7%) of single cluster 1 and 8/115 (7.0%) of single cluster 2 infections (p = 0.208). There was no clinically significant difference in outcome between the two subpopulations. Cluster 1 infections were more likely to be associated with peri-domestic activities while cluster 2 were associated with interior forest activities consistent with the preferred habitats of the respective macaque hosts. Infections with both P. knowlesi subpopulations cause a wide spectrum of disease including potentially life-threatening complications, with no implications for differential patient management.